Phytotherapeutic Potential Of Bauhinia Racemosa In A Topical Lotion For Bacterial Infections - Latala, Virendra Singh; Nama, Nitin; Gupta, M. K.; Vyas, Girish Kumar (Journal of Neonatal Surgery, 2025)
Introduction: Bacterial skin infections remain a public health challenge, particularly with the rise in antibiotic resistance. Traditional medicinal plants like Bauhinia racemosa have shown promise due to their phytochemical-rich profile and ethnomedicinal relevance. Objective: This study aimed to formulate and evaluate a topical lotion containing Bauhinia racemosa leaf extract for its antibacterial potential and physiochemical stability. Methods: Dried Bauhinia racemosa leaves were extracted using ethanol in a Soxhlet apparatus. Phytochemical screening identified flavonoids, tannins, alkaloids, saponins, and terpenoids. Characterization was done using TLC and UV-Visible spectroscopy. The extract was formulated into an oil-in-water lotion and evaluated for pH, viscosity, spreadability, homogeneity, and stability over 90 days. Antibacterial activity was tested using agar well diffusion, disc diffusion, and broth dilution (MIC) methods against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. Results: The lotion demonstrated effective antibacterial activity, especially against S. aureus, and retained favorable pH (4.5–6.8), viscosity, and appearance over 90 days. No phase separation or microbial contamination was observed. Conclusion: The topical formulation of Bauhinia racemosa shows promising antibacterial efficacy and stability, supporting its use as a cost-effective, natural alternative for managing skin infections.